2D location biases depth-from-disparity judgments but not vice versa. Issue 9 (26th November 2017) - Finlayson, Nonie J.; Golomb, Julie D.
ABSTRACT: Visual cognition in our 3D world requires understanding how we accurately localize objects in 2D and depth, and what influence both types of location information have on visual processing. Spatial location is known to play a special role in visual processing, but most of these findings have focused on the special role of 2D location. One such phenomena is the spatial congruency bias, where 2D location biases judgments of object features but features do not bias location judgments. This paradigm has recently been used to compare different types of location information in terms of how much they bias different types of features. Here we used this paradigm to ask a related question: whether 2D and depth-from-disparity location bias localization judgments for each other. We found that presenting two objects in the same 2D location biased position-in-depth judgments, but presenting two objects at the same depth (disparity) did not bias 2D location judgments. We conclude that an object's 2D location may be automatically incorporated into perception of its depth location, but not vice versa, which is consistent with a fundamentally special role for 2D location in visual processing.